Analisis Pemasangan Filter Pasif Untuk Mengurangi Harmonisa Pada Transformator Rectifier Di PT. Indah Kiat Pulp And Paper Perawang - Rido Rahmadani; Atmam Atmam; Elvira Zondra (Teknik Elektro Universitas Lancang Kuning, 2019)
The chlor-alkali process is an electrolysis process which plays an important role in the chemical industry such as the pulp industry. The process produces a product in the form of H2 gas, CL2 gas and NaOH (where the source of chloride ion used is NaCl). This electrolysis process requires a dirrect current with a large current and a low voltage. In this electrolysis process a three phase controlled 12 pulse rectifiers are used which a connected with multi-winding transformers. In the rectifiers process there will be harmonic distortion on the source side of the transformer which can reduce the power quality of the system. To overcome the harmonic problems that occur in the system, an installation analysis of the equipment in the form of a passive single tuned filter is aimed at reducing harmonic distortion of current and voltage and increasing the power factor (cos φ). From the result of harmonic analysis using ETAP software, after the installation of harmonic filters orde 11, 13 and 23, the harmonic current value (THDI) and harmonic voltage (THDV) has decreased, namely, before the filter installation, THDI value is 6,5% whereas after installation of filters, THDI value becomes 0,98%, thus there is a THDI decrease of 5,52%. Furthermore, for the voltage harmonic value (THDV) before filter installation is 1,48% while after filtering, THDV value becomes 0,26%, thus there is a THDV decrease of 1,22%. From the results of the simulation of the flow of power (load flow analysis), after installation of filters there is an increase in the value of the power factor (cos φ). Namely, before the filter installation, the value of power factor (cos φ) is 0,8 while after the filter installation the value of the power factor (cos φ) to 0,96, thus an increase in the power factor (cos φ) of 16%. Keywords : harmonic filter, single tuned filter, power factor, transformer rectifier